DETERMINAN FINANCIAL STATEMENT FRAUD DENGAN MENGGUNAKAN PENDEKATAN FRAUD TRIANGLE - Yeasy Darmayanti; Ilham Setiawan; Ethika Ethika (AKUNTABILITAS, 2019)
The aim of this study is to examine the effects of financial stability, external pressure, personal financial needs, financial targets, nature of industry, ineffective monitoring, and rationalization of financial statement fraud on manufacturing companies listed on the Indonesia Stock Exchange from 2012 to 2016 .From a population of 159 listed manufacturing companies, 72 samples were obtained that met the criteria. Testing using SPSS version 23 for logistic regression analysis. The results of this study indicate that external pressure and nature of industry have a significant influence on financial statement fraud. On the other hand, financial stability, personal financial need, financial targets, ineffective monitoring and rationalization have no effect on financial statement fraud.